2015
DOI: 10.1002/adsc.201500186
|View full text |Cite
|
Sign up to set email alerts
|

Practical Solvent‐Free Ruthenium Trichloride‐Mediated Benzannulation Approach to Fused Functionalized Arenes

Abstract: Thes olvent-andl igand-free [2+ +2+ +2] ruthenium-promoted cycloaddition of a,wdiynes and alkynes provides af acile and efficient strategy for the synthesis of substitutedb enzene-derived systems.T he search for the optimal reaction conditions revealedt he unprecedented catalytic activity of ruthenium trichloridef or benzannulation reactions and this atom-economicalp rocess allowed the synthesis of fused arenes including dihydrobenzofurans,i soindolines,i ndanes in good to high yields.T his practical protocola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The authors observed that the microwave irradiation enhanced the reactivity; however, it did not affect the regioselectivity [224] . Amide‐tethered diynes, [225] N ‐benzenesulfonamide 1,6‐diynes, [226] and bis‐1,3‐diynes [227] were used as efficient substrates to [2+2+2] cycloisomerization reactions to give the corresponding isoindolines in good yields.…”
Section: Synthesis Of Isoindolinesmentioning
confidence: 99%
“…The authors observed that the microwave irradiation enhanced the reactivity; however, it did not affect the regioselectivity [224] . Amide‐tethered diynes, [225] N ‐benzenesulfonamide 1,6‐diynes, [226] and bis‐1,3‐diynes [227] were used as efficient substrates to [2+2+2] cycloisomerization reactions to give the corresponding isoindolines in good yields.…”
Section: Synthesis Of Isoindolinesmentioning
confidence: 99%
“…254 Finally, in 2015 and 2016, Ratovelomanana-Vidal and Michelet developed a cost-effective intermolecular [2+2+2] cycloaddition of α,ω-diynes with alkynes to construct benzene and fluorenone derivatives, catalyzed by RuCl 3 •nH 2 O in the absence of ligand under solvent-free conditions (not shown). 255,256 3.2.3. [2+2+2] Cycloadditions of Alkynes+Alkenes.…”
Section: [2+2+2]mentioning
confidence: 99%
“…In contrast, in 2012 Holthausen and Ghosh explored the use of arachno -[(Cp*RuCO) 2 B 2 H 6 ] as a catalyst for intermolecular alkyne cyclotrimerization, and their computational studies implicated a mechanism in which the transient ruthenacyclopentadiene is converted to a benzene derivative through a Diels–Alder-type [4+2] cycloaddition with the third alkyne (not shown) . Finally, in 2015 and 2016, Ratovelomanana-Vidal and Michelet developed a cost-effective intermolecular [2+2+2] cycloaddition of α,ω-diynes with alkynes to construct benzene and fluorenone derivatives, catalyzed by RuCl 3 ·nH 2 O in the absence of ligand under solvent-free conditions (not shown). , …”
Section: Six-membered Ring Formationmentioning
confidence: 99%
“…This procedure was applied on the gram-scale without sacricing the yield or outcome of the methodology. 19 Other applications of Ru catalysts in [2 + 2 + 2] cycloaddition of di(3-iodopropargyl)amine with alkynes to afford 4,7-diiodoisoindoline derivatives are also known. 20 Yamamoto and co-workers were able to demonstrate that a series of regioisomeric isoindolinones 28 and 29 be efficiently synthesized from the cyclization of amide-tethered diynes 27 with terminal alkynes 6 by treatment with [Cp*Ru(cod)Cl] in DCM.…”
Section: Isoindolinesmentioning
confidence: 99%